(3eQTO GdRhGQ Edi bHhQ GdCHQGQs - (3Rjf GdOjf YKeGf Hf Gdehabs ((3TgGH GdOjf Hf GdMGL TgGH GdOjf GdSQfLj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQa LHd GdebWe Hcd eSLO TQja eYXe s
(3BNQgG (B:s
(3bGd cGf eMeO Hf GHj HcQ Qaj Gddg JYGdj Yfg bO GUjH QMeg Gddg JYGdj QMeI hGSYI GeG hGdgd Gf cGf cef jDef HGdbVGA baUd gPG cJGH PcQJ ajg aVd RjGQI GdbHhQ hGOGHgG hPcQJ ajg aVd LHd GdebWe s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs